A New Order of Things : Origins of a Nurse Practitioner Movement - Freund, Cynthia M. (Book collections on Project MUSE., 2022)
"A New Order of Things provides many lessons on change and innovation adoption, lessons told through the stories of the core innovators who took the nurse practitioner idea from a clinic experiment to a university program at the University of North Carolina at Chapel Hill and extended that to two additional educational programs across the state of North Carolina, and to a partnership with community leaders developing rural clinics dotting its rural state"--